Problems of Arabic Language Education in the Society 5.0 Era - M. Dzaki Sholihin; Marhamah Salwa; Sonya Rizla Kusuma; Sakholid Nasution (Young Journal of Social Sciences and Humanities, 2025)
This research aims to identify the importance of Arabic as the main foundation in understanding Islamic teachings, especially the Qur'an, hadith, and Islamic literature. This study highlights the challenges and opportunities for learning Arabic in the modern era which is characterized by technological advances and digitalization. It was emphasized that learning Arabic is a crucial element in Islamic education in order to maintain the relevance of Islamic values in the midst of changing times. This study uses a qualitative method based on Library Research by collecting data from books, journals, articles, and official documents. The results of the analysis show that Arabic plays a significant role in facing the Society 5.0 era, not only as a means of communication, but also as the main link to explore Islamic teachings. Recommendations include curriculum development, the application of innovative methods, and adaptation to the dynamics of the times in order